Phylogenetic placement of the mysterious Malagasy genus Ambrella H. Perrier (Vandeae, Orchidaceae) - Nowak, Sławomir; Górniak, Marcin; Olędrzyńska, Natalia; Baranow, Przemysław; Szlachetko, Dariusz L. (Frontiers in Plant Science, 2025)
IntroductionThe monotypic genus Ambrella H. Perrier, endemic to Madagascar and traditionally placed within the subtribe Angraecinae, has long poses a challenge in terms of its phylogenetic classification.MethodsTo clarify the evolutionary position of Ambrella, analyzed nuclear (ITS) and plastid (matK) markers applying maximum likelihood methods for phylogenetic inference and estimating divergence times using a Bayesian relaxed molecular clock model implemented in BEAST.ResultsOur results show that Ambrella forms a strongly supported clade with the Malagasy genera Cryptopus Lindl., Oeonia Lindl., and Neobathiea Schltr. Despite the phylogenetic proximity, Ambrella remains morphologically distinct, particularly in terms of its floral architecture. According to molecular dating, the lineage leading to Ambrella diverged during the Late Miocene to Early Pliocene (ca. 8.8–3.3 Mya), a period of substantial ecological change in Madagascar.DiscussionThe results of this study provide new insight into the evolutionary history of Ambrella and clarify its phylogenetic position within Vandeae. Despite forming a well-supported clade with other Malagasy genera such as Cryptopus, Oeonia, and Neobathiea, Ambrella maintains clear morphological distinctiveness, particularly in its floral architecture. This suggests that its most striking morphological features may have evolved independently.